The Role and Position of the Mother in the Family Al-Qur'an Perspective (Study of the Story of Maryam) - Nurhaliza Putri Maulida; Raihanah Raihanah; Noor Ainah; Halimatussa'diyah Halimatussa'diyah; Mahmud Yusuf (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study discusses the role and status of mothers in the family based on the story of Maryam bint Imran from the perspective of the Qur’an. Islam places mothers in a strategic position, not only as biological figures who give birth and nurse, but also as educators, character builders, and guardians of spiritual values within the family. The study employs a library research method with a descriptive qualitative approach, using the tafsir tahlili method, which interprets the Qur’anic verses sequentially and contextually. The findings reveal that Maryam’s role includes dedicating her child for the sake of religion, providing proper education and a good name, praying for her child, preserving her chastity, and enduring pregnancy and childbirth with steadfast faith. In the Qur’an, the status of mothers is exalted due to their piety, spiritual strength, and contribution to nurturing a faithful generation. The story of Maryam affirms that Allah Almighty chose the family of Imran as the best family and selected Maryam above all other women on earth.